(untitled) (Journal of Hama University, 2024)
This research aims to assess the relevance of the economic value-added strategy in the formation of investment portfolios for companies listed at Amman Stock Exchange, and compare it with the market portfolio in terms of returns and risks during the period (2017-2021). To achieve this goal and after calculating the economic value added of the companies, we form a portfolio of companies with high economic values and a portfolio of companies with low economic values for each year, then calculate the returns and risks of these portfolios. In addition, we calculate the returns and risks of the market portfolio during the study period and compare them together. The research finds that there are no statistically significant differences between the returns of the high and low economic value-added portfolios and the returns of the market portfolio on Amman Stock Exchange, and the market portfolio achieves the lowest risks during the same period. This research recommends that investors should invest in companies with low economic value added in Amman Stock Exchange.